If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(4 + 3x) = 8x + 14 5x + (4 * -1 + 3x * -1) = 8x + 14 5x + (-4 + -3x) = 8x + 14 Reorder the terms: -4 + 5x + -3x = 8x + 14 Combine like terms: 5x + -3x = 2x -4 + 2x = 8x + 14 Reorder the terms: -4 + 2x = 14 + 8x Solving -4 + 2x = 14 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + 2x + -8x = 14 + 8x + -8x Combine like terms: 2x + -8x = -6x -4 + -6x = 14 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + -6x = 14 + 0 -4 + -6x = 14 Add '4' to each side of the equation. -4 + 4 + -6x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + -6x = 14 + 4 -6x = 14 + 4 Combine like terms: 14 + 4 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| a=-11+7(34) | | 8c+3+48c-120= | | m^3+216m^3= | | 6+3(K-4)=20 | | 8(4x-4)=-5k-32 | | b-3(b-4(1-b))=54 | | 3.5+k=8.0 | | 112=7b | | 0.9a=5a | | m^3+216n^2= | | 3n^2+22n+32=0 | | 4m+9=6m-5 | | a=-11+7(4) | | -P+11=5P-13 | | a=-11+7(3) | | X-17=22 | | 18z=16z | | 2n^2+17=-26 | | X+9=25 | | 3b-b= | | .05(x-200)=240 | | X+86=47 | | .5(4x+20)=6(x-1) | | 2n^2+17+26=0 | | -24=6w+5(w-7) | | a=-11+7(2) | | -B+7=2B-8 | | X=3+-1b | | y=2(6)-4 | | -5(x-3)=4-2(x+1) | | X-63=17 | | 9x+15=48 |